Fibrinogen status in relapse and remission of childhood nephrotic syndrome - Veronica Lily Limantara; Ida Bagus Mudita; I Ketut Suarta (Indonesian Pediatric Society Publishing House, 2016)
Objective To evaluate fibrinogen concentration of relapsing neph- rotic syndrome (NS) in children, and to investigate relationship between fibrinogen with albumin and cholesterol. Methods A cross-sectional study among NS patients admitted to pediatric outpatient clinic and pediatric ward at Sanglah Hospital, Denpasar, from November 1, 2003 to January 31, 2004. All pa- tients were evaluated for clinical and laboratory findings of relapse and remission, including edema, proteinuria, serum albumin, total cholesterol, as well as total platelet count and fibrinogen concen- tration to evaluate coagulation parameters in nephrotic patients. Results There were 36 patients with the mean age of 7.4 (SD 2.3) years included in this study. Mean fibrinogen concentration in re- lapse state was 671.8 (SD 102.7) mg/dl, while in remission state was 255.2 (SD 50.5 mg/dl); the mean difference was 416.6 mg/dl (95% CI 362.9;470.4; P<0.001). Fibrinogen was inversely and strongly correlated with serum albumin concentrations (r=-0.91; P<0.001). Fibrinogen was positively and strongly correlated to to- tal cholesterol (r=0.80; P<0.001). Using multiple regression analy- sis, it was shown that only relapse/remission status was signifi- cantly associated with fibrinogen concentration (P<0.001). Conclusion Fibrinogen status is significantly correlated with re- lapse and remission status of NS in childhood patients.